BARRIERS TO EFFECTIVE EDUCATION OF STUDENTS WITH SEVERE AND PROFOUND MULTIPLE DISABILITIES IN BULGARIA AND FLANDERS - Magdalena Hadzhieva (Педагогически форум)
The education of students with severe and profound multiple disabilities is one of the most discussed topics in the contemporary special education worldwide. The educational systems seek to create and implement effective models of organization of the educational process in order to ensure access to education and qualitative support for personal development. This article aims to present the educational inclusion of students with severe and profound multiple disabilities in Bulgaria and Flanders and discusses the barriers to effective education of children based on empirical study of the views and opinions of pedagogical specialists in both educational systems.